PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI: Studi pada Dinas Pemberdayaan Masyarakat dan Desa di Kabupaten Majalengka (Universitas Majalengka, 2022)
This research aims to analyze organizational culture factors and work motivations their influence on employee performance. The study used quantitative methods by testing hypotheses about the influence of organizational culture and work motivation on employee performance simultaneously and partially. The sample in this study was all 32 active employees using a stratification system based on groups and positions. The results proved that organizational culture and work motivation positively influence employee performance both simultaneously and partially